Loxapine and Cyproheptadine Combined Limit Clozapine Rebound Psychosis and May Also Predict Clozapine Response - Lila Aboueid; Richard H. McCarthy (Case Reports in Psychiatry)
Clozapine has been consistently shown to be superior to other antipsychotics in the treatment of psychosis. However, clozapine usage has been limited due to required routine blood monitoring and the potential for life threatening side effects. We report a case of a 66-year-old female patient, who developed clozapine-induced agranulocytosis after 10 weeks of clozapine treatment and was subsequently successfully treated with a combination of loxapine and cyproheptadine. The combination is thought to mimic the pharmacological profile of clozapine, rendering it as a possible alternative to traditional clozapine treatment.